THE IMPLEMENTATION OF TEACHER CORRECTIVE FEEDBACK IN TEACHING WRITING DESCRIPTIVE TEXT TO THE SECOND YEAR STUDENTS OF SMP N 1 TUNJUNGAN IN 2010 /2011 ACADEMIC YEAR - RUKMINI, ATIK SRI (2011)

(untitled)
This study is aimed at describing: 1) the implementation of teaching writing descriptive genre using teacher corrective feedback, 2) the student’s response to the writing teaching- learning process, and 3) the problems faced by the teacher. In achieving the objectives, the researcher used descriptive qualitative as the approach to collect and analyze the data. The research was held in SMP N 1 Tunjungan. The research took 40 students of the second year students as the subject of the study. The writer gets the data of the research from event, informant, and document. The techniques of collecting d are the observation ata and interview about the writing teaching- learning process. The result of the analysis shows that teacher corrective feedback technique is appropriate and effective for the second year student of SMP N 1 Tunjungan in teaching writing descriptive genre. By using this technique, the students are capable to know ing their errors, the reason and correct it. So, it can accelerate the teaching- learning writing process. They are interested, enthusiastic, and motivated to take part in the classroom activities. They are not bored and more entertained in the classroom, because the teacher also provided a picture and real object to be described as the medium of teaching. The teacher has several problems in teaching namely difficult y in explaining the content of the text, students’ difficulties in developing paragraph in descriptive text, students’ difficulties in mastering component of writing, and lacking of media.